Author Correction: High-dimensional single-cell analysis predicts response to anti-PD-1 immunotherapy. (November 2018) - Krieg, Carsten; Nowicka, Malgorzata; Guglietta, Silvia; Schindler, Sabrina; Hartmann, Felix; Weber, Lukas; Dummer, Reinhard; Robinson, Mark; Levesque, Mitchell; Becher, Burkhard
In the version of this article initially published, Figs. 5a, c and 6a were incorrect because of an error in a metadata spreadsheet that led to the healthy donor patient 2 (HD2) samples being used twice in the analysis of baseline samples and in the analysis at 12 weeks of anti-PD-1 therapy, while HD3 samples had not been used.